Detection of Copper Bisguanidine NO Adducts by UV-vis Spectroscopy and a SuperFocus Mixer - Oppermann, Alexander; Laurini, Larissa; Etscheidt, Fabian; Hollmann, Katharina; Strassl, Florian; Hoffmann, Alexander; Schurr, Daniela; Dittmeyer, Roland; Rinke, Günter; Herres-Pawlis, Sonja (Chemical Engineering & Technology)
Abstract The reaction of Cu(I) bisguanidine complexes with nitric oxide and the formation of intermediate species were monitored via UV-vis spectroscopy at low temperature, with the occurrence of characteristic absorption bands. The origin of the emerging species and their character were substantiated by electron paramagnetic resonance (EPR) measurements and density functional theory (DFT) studies showing a delocalized {CuNO}11 radical species. Furthermore, this system was transferred to the SuperFocus mixer setup, which allows rapid mixing and the determination of decay constants at ambient temperatures of the thermally sensitive species. However, these experiments demonstrated the limits of these systems, such as the NO saturation in organic solvents and a preferably precise temperature control within the SuperFocus mixer, which should be addressed in the future.
Keywords: Copper guanidine complexes; Nitric oxide; SuperFocus mixer